APLIKASI SIG UNTUK PENETAPAN KESESUAIAN WILAYAH PENERAPAN MEKANISASI PERTANIAN TANAMAN PANGAN - Mubekti, Mubekti (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
The study is the preliminary research aiming to apply the usefulness of the GISsystem for classifying suitability of region to the agricultural mechanization. Simplebasic theory of GIS and classification of agricultural mechanization were presented.Nine physical and non-physical parameters as limiting factors were defined and aweight of each parameter was calculated in order to know how far its effect to theagricultural mechanization practice. Data coming from several types, ie: numeric,vector and remote sensing (raster) were prepared to support the process. Twoordoes consisting of five classes were employed to extract suitability classificationof each District in Jawa Barat dan Banten Province. The results show that tendistricts are classified into suitable for applying agricultural mechanization, and therest ten districts are classified into not suitable. Depending on the dynamic characterof limiting factor, suitability class would possibly change along the time. Saveralconclusions and advices for improving research are given.